O acolhimento a demandas relacionadas ao comportamento suicida na Atenção Primária à Saúde sob o enfoque analítico-comportamental - Andrade, Maria Vanesse (2022)
Suicidal behavior is a complex and multifactorial phenomenon. Different areas of knowledge have made efforts to improve health interventions for suicide prevention. Research on the subject has sought to identify risk and protective factors, as well as triggering epidemiological, social and behavioral aspects, especially after the World Health Organization (WHO) identified suicide as a public health problem and indicated the possibility of prevention in up to 90% of cases. In the context of public health, access for people who present some type of suicidal behavior occurs mostly through urgency/emergency networks (tertiary care/hospitals) and continuing care networks (Primary Health Care (PHC)/Basic Units). of Health (UBS). The present work aims to: (1) carry out a survey of studies on the care of people in PHC and how this care is performed in terms of screening, risk classification and referrals; (2) to evaluate the documents and technical regulations that govern the flow of reception care in PHC in the Brazilian context; (3) identify possible contingencies from the recommended procedures for reception, especially in meeting demands related to suicidal behavior in PHC; (4) to develop, based on the survey carried out and on the identified contingencies, a selfinstructive support material based on Behavior Analysis aimed at professionals who work in reception in PHC